INCREASING THE ROLE OF AGRICULTURAL EXTENSION PROGRAMS IN POVERTY ALLEVIATION AND WIDE PROMOTION IN THE ECONOMY (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article aims to review research on the role of agricultural extension programs in poverty alleviation. Various approaches and tools used in agricultural extension program implementation were discussed and ways to enhance their contribution to poverty alleviation were highlighted.